Prevalence and risk factors of polyomavirus BK replication in simultaneous pancreas/kidney transplant recipients from a single transplant center - Mindlova, Martina; Boucek, Petr; Saudek, Frantisek; Skibova, Jelena; Jedinakova, Teodora; Lipar, Kvetoslav; Adamec, Milos; Hirsch, Hans H (Clinical transplantation, 2012)
BACKGROUND: BK virus (BKV) replication is considered as a marker of risk for polyomavirus BK-associated nephropathy (PVAN). We evaluated the occurrence and risk factors for BKV DNA positivity following simultaneous pancreas/kidney transplantation (SPK). METHODS: Point prevalence of BK viruria and viremia was assessed in 183 SPK recipients. Real-time polymerase chain reaction was used with a detection threshold of 10(3) copies/mL. High-level BKV positivity was defined as viruria and/or viremia >10(7) and >10(4) copies/mL, respectively. BKV-positive patients were retested after 4-13 months and underwent an additional six-month clinical follow-up. RESULTS: Urine and serum BKV positivity was detected in 28 (17.3% of available samples) and 7 (3.8%) patients, with high-level viruria and viremia occurring in 6 (3.7%) and 3 (1.6%) patients, respectively. PVAN was biopsy-confirmed in 1 and suspected as a cause of progressive renal failure in another SPK recipient. Patients with single low-level viruria did not progress to high-level positivity or PVAN at follow-up. In multivariate analysis, pre-transplant diabetes duration and delayed graft function were independently associated with BKV positivity. CONCLUSIONS: Point prevalence of high-level BKV positivity and PVAN was low in SPK recipients from a single center. Diabetes duration and delayed graft function were independent risk factors for BKV replication.
Keywords: kvantitativní polymerázová řetězová reakce; DNA virů; virus BK; lidé středního věku; Female; Real-Time Polymerase Chain Reaction; mužské pohlaví; Kidney Transplantation; rizikové faktory; DNA, Viral; Tumor Virus Infections; Viremia; Pancreas Transplantation; transplantace slinivky břišní; Humans; dospělí; virová nálož; Viral Load; infekce onkogenními viry; BK Virus; polyomavirové infekce; transplantace ledvin; lidé; nemoci ledvin; Middle Aged; viremie; Polyomavirus Infections; ženské pohlaví; Virus Replication; Risk Factors; replikace viru; Adult; Male; Kidney Diseases